INTELLIGIBILITY IN CONTEXT SCALE AS A TOOL FOR A QUICK AND RELIABLE ASSESSMENT OF CHILDREN'S SPEECH EFFICIENCY - Martina Ozbič (The Society for Children with Metabolic Disorders, 2023)
In preschoolers, we can observe speech discrepancies very frequently. Atypical discrepancies are important in children's speech intelligibility and, consequently, their communication self-esteem. For better prevention and early detection of sound speech disorders, there is a valid, reliable and evaluated parent-report questionnaire for speech intelligibility evaluation (ICS-Intelligibility in Context Scale questionnaire). The paper describes the statistically significant correlations (0,448  0,651) between the subjective description of intelligibility (ICS score) and objective quantification of speech accuracy (whole word matching) and the reliability of the Slovenian version of the questionnaire, tested on 93 2  6-year-old preschool Slovenian children (Cronbach's alpha 0,947). The questionnaire is a reliable and helpful tool in the paediatric clinic for the first screening of speech and the child's intelligibility. Although the use of the ICS tool does not replace the role of a detailed speech and language therapist's evaluation, it allows a quick and functional evaluation of the impact of the speech on a child's communication in everyday life.